2018
DOI: 10.3892/etm.2018.6476
|View full text |Cite
|
Sign up to set email alerts
|

Complement 3 glomerulonephritis in rheumatoid arthritis: A case report and follow‑up

Abstract: Abstract. Glomerulonephritis (GN) caused by rheumatoid arthritis may manifest as various pathological types; however, to the best of our knowledge, rheumatoid arthritis-associated complement 3 (C3)-GN has not been reported by any previous studies. C3GN is caused by dysregulation of the alternative pathway of complements, which is completely different from activation of the classic pathway of a typical autoimmune disease to cause renal damage. The present study describes a patient with a history of rheumatoid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A few previous studies have reported the coexistence of C3GN in the setting of autoimmune diseases, including patients with SLE or with SLEassociated autoantibodies, [15][16][17] ANCA-associated vasculitis, 19 rheumatoid arthritis and autoimmune thyroiditis. 20 These findings suggest the presence of a subgroup of patients whose C3GN may be related to autoimmunity. 15 The presence of C3NeF, identified in approximately 50% of patients with C3GN, indicates the existence of autoantibodies against C3 convertase that could stabilize the complex and cause persistent activation of the alternative complement pathway 21 ; however, our patient tested negative.…”
Section: Discussionmentioning
confidence: 85%
“…A few previous studies have reported the coexistence of C3GN in the setting of autoimmune diseases, including patients with SLE or with SLEassociated autoantibodies, [15][16][17] ANCA-associated vasculitis, 19 rheumatoid arthritis and autoimmune thyroiditis. 20 These findings suggest the presence of a subgroup of patients whose C3GN may be related to autoimmunity. 15 The presence of C3NeF, identified in approximately 50% of patients with C3GN, indicates the existence of autoantibodies against C3 convertase that could stabilize the complex and cause persistent activation of the alternative complement pathway 21 ; however, our patient tested negative.…”
Section: Discussionmentioning
confidence: 85%